Drug Development in Alzheimer’s Disease: The Contribution of PET and SPECT - Declercq, Lieven D.; Vandenberghe, Rik; Van Laere, Koen; Verbruggen, Alfons; Bormans, Guy (Frontiers in Pharmacology, 2016)
Clinical trials aiming to develop disease-altering drugs for Alzheimer’s disease (AD), a neurodegenerative disorder with devastating consequences, are failing at an alarming rate. Poorly defined inclusion- and outcome criteria, due to a limited amount of objective biomarkers, is one of the major concerns. Non-invasive molecular imaging techniques, positron emission tomography and single photon emission (computed) tomography (PET and SPE(C)T), allow visualization and quantification of a wide variety of (patho)physiological processes and allow early (differential) diagnosis in many disorders. PET and SPECT have the ability to provide biomarkers that permit spatial assessment of pathophysiological molecular changes and therefore objectively evaluate and follow up therapeutic response, especially in the brain. A number of specific PET/SPECT biomarkers used in support of emerging clinical therapies in AD are discussed in this review.